Structural rehabilitation of API steel pipes using GFRP under dynamic condition - Mohd Hisbany Mohd Hashim,; Mohd Fakri Muda,; Nurhakim Hazman Norhan,; Muhammad Daniel Abdul Shahid,; Najwa Mohammad Fadzil,; Abdul Rahman Mohd Sam,; Amin Al-Fakih, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Corrosion of steel pipes significantly challenges industries such as oil and gas, water transport, and chemicals, where pipeline integrity is paramount. Degradation due to corrosion leads to reduced efficiency, heightened risk of catastrophic failure, and substantial economic and safety concerns. This study investigates the effectiveness of Glass Fiber-Reinforced Polymer (GFRP) wrap in restoring and enhancing the performance of corroded API 5L X42 steel pipes. Through controlled corrosion induction, application of GFRP wrapping, and cyclic loading tests, this study offers a comprehensive understanding of the initial response and performance under dynamic condition. For unrepaired pipes, maximum force applied ranged from 67.84 kN to 404.8 kN as stroke increased from 1mm to 12mm, with corresponding maximum deformation from 0.8mm to 9.01mm. In contrast, GFRP-rehabilitated pipes demonstrated applied force ranging from 28.98 kN to 452.87 kN, with maximum deformation from 0.65mm to 14.41mm. These findings underscore the efficacy of GFRP patches in mitigating corrosion effects, extending pipeline service life, and reducing failure risk. This study validates theoretical models and offers practical guidance for adopting resilient materials in engineering, enhancing pipeline integrity in critical industrial applications.